2019
DOI: 10.3390/molecules24142605
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of SiO2-MnFe2O4 Composites via One-Pot Hydrothermal Synthesis Method and Microwave Absorption Investigation in S-Band

Abstract: MnFe2O4 NPs are successfully decorated on the surface of SiO2 sheets to form the SiO2-MnFe2O4 composite via one-pot hydrothermal synthesis method. The phase identification, morphology, crystal structure, distribution of elements, and microwave absorbing properties in S-band (1.55~3.4 GHz) of the as-prepared composite were investigated by XRD, SEM, TEM, and Vector Network Analyzer (VNA) respectively. Compared with the pure MnFe2O4 NPs, the as-prepared SiO2-MnFe2O4 composite exhibits enhanced microwave absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 52 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…The constituents, as evident from the corresponding EDS spectra in Fig. 2 b, are Mn, Fe and Yin et al 32 found that the grains are stacked with thick laminar structured silica. This behaviour is evident from Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The constituents, as evident from the corresponding EDS spectra in Fig. 2 b, are Mn, Fe and Yin et al 32 found that the grains are stacked with thick laminar structured silica. This behaviour is evident from Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Another research group, Y. Wang et al [ 36 ] observed the maximum reflection loss of −32.8 dB at 8.2 GHz with the thickness of 3.5 mm for MnFe 2 O 4 /RGO composite. Further, P. Yin et al [ 37 ] noticed the maximum reflection loss of −14.87 dB at 2.25 GHz with the thickness of 4 mm. Furthermore, Y. Wang et al [ 38 ] showed the maximum absorption of -38 dB at 6 GHz with the thickness of 3.5 mm for a ternary composite of Ag/MnFe 2 O 4 /reduced graphene oxide (RGO).…”
Section: Resultsmentioning
confidence: 99%
“…where ε and ε are, respectively, the real and the imaginary part, and j the imaginary unit. The real part of permittivity (ε ) is also known as the dielectric constant and it represents the energy storage capacity of a material exposed to an electromagnetic field or, in other words, the ability to polarize [32]. The charged molecules contained within materials, under an electromagnetic field, try to orientate following the field and storing electromagnetic energy [6].…”
Section: Elements Of Dielectric Theorymentioning
confidence: 99%